Penerapan Supply Chain Management (SCM) Dalam Pemantauan Stok Barang Berbasis Web - Sri Wahyuni Nasution; Nuriadi Manurung; Elly Rahayu (Building of Informatics, Technology and Science (BITS), 2022)
Umi Nala Shop store is engaged in selling toys, such as floats, laptop screens, construction sets, ambulance cars, small cars, jeep cars, and many more. The problem is that this store does not know the amount of inventory of goods in the warehouse. This store purchases goods from suppliers for the inventory of goods to be sold without knowing the available stock. This makes the inventory of goods to be sold by the store uncontrollable. The store records incoming and outgoing goods and transactions manually using paper so that data can be lost. The Umi Nala Shop has more than 200 resellers but is inactive and has ten suppliers to supply the goods sold. The sale of goods at the Umi Nala Shop is still offline, where customers come directly to the Umi Nala Shop. Marketing is carried out through social media networks such as Facebook, WhatsApp, and Instagram. In carrying out its business, it is necessary to pay attention to inventory management to provide for consumer needs and control inventory when there is a high demand for goods. For the store to compete, it is necessary to implement Supply Chain Management (SCM) to integrate suppliers, warehouse manufacturing, and storage so that goods are distributed in the correct quantity at the right time, to minimize costs and provide satisfaction to consumers. The purpose of this study is to build an SCM application that can make it easier for stores to find out the amount of inventory to ensure the availability of goods. The results of this study with the implementation of Supply Chain Management at the Umi Nala Shop store can help and make it easier for store owners to manage the supply chain of goods.